Impact of political parties sites on the network "Facebook" On the participation of Arab youth in the general elections - AbdelRahman, AbdelSalam Mohamed Sayed (Arab Journal for Sciences and Research Publishing, 2019)
The aim of the study is to identify the interest and follow-up of the Arab youth to the pages of the political parties on Facebook, and to identify the habits, patterns and motives of the uses of Arab youth, as well as the interactive activities carried out on the pages of the political parties and to identify the confidence of Arab youth and their dependence on party pages on Facebook, and identify the impact of the Arab youth on those pages on their participation in the general electionsThe study was based on a descriptive study. The field study was conducted on a sample of 400 Arab youth who were active in the Facebook in the age group (18-40 years) Through the electronic questionnaireThe study concluded:-  Male respondents use Facebook more than females (61% for males versus 46.5% for females).- There are differences between males and females in the forms of participation in the general elections based on their follow-up to the pages of political parties on Facebook depending on the nationality variable and variable monthly income, and educational level.- The male respondents were more political than the females, at 26% compared to 18.5% for females.
Keywords: Facebook; Arab youth; Political parties; General elections